Oropharyngeal lesions and cervical lymphadenopathy: syphilis is a differential diagnosis that is still relevant. Issue 8 (11th August 2010) - Ikenberg, Kristian; Springer, Erik; Bräuninger, Wolfgang; Kerl, Katrin; Mihic, Daniela; Schmid, Simone; Schmitt, Anja; Yeginsoy, Sibel; Bode, Beata; Weber, Achim
Abstract : Background: Syphilis (lues), a chronic infectious disease caused by Treponema pallidum, has been increasing in incidence during the last few years. Therefore, while clinically it is often not suspected, syphilis is increasingly becoming a differential diagnosis in routine pathology. Aim: To report our experience with five cases of cervical lymphadenopathy and/or oropharyngeal lesions, clinically thought to be lymphomas, lymph node metastases or carcinoma, in which we made the mostly clinically unsuspected diagnosis of syphilis. Methods: Fine needle aspiration of enlarged cervical lymph nodes was evaluated by cytology and flow cytometry (fluorescence-activated cell sorting analysis), and biopsies were examined by using histology. In addition, all materials were also subjected to immunostaining, silver staining and molecular (PCR) testing. Results: Fine needle aspiration cytology revealed follicular hyperplasia in two cases and granulomatous lymphadenitis in one case. In three patients, concomitant biopsy of co-existing oropharyngeal lesions revealed histological findings compatible with syphilis. T pallidum was detected in all cytological and histological samples by immunohistochemistry/immunocytochemistry and PCR. Subsequently, a diagnosis of syphilis was confirmed clinically and by serology. Conclusions: Syphilitic lymphadenitis is still a relevant differential diagnosis of cervical lymphadenopathy, and it is clinically often not suspected. Co-exisiting oropharyngeal lesions should alert the physician to this differential diagnosis; and lesions with compatible morphology should be tested with immunohistochemistry and immunocytochemistry and/or molecular analysis to confirm the diagnosis of syphilis.